Faktor-Faktor yang Mempengaruhi Keterlambatan Rekapitulasi Penghitungan Suara pada Pemilu Tahun 2019 - Dana Permana; Muhammad Arif Nasution; Arifin Saleh Siregar (Universitas Medan Area, 2021)
The delay in recapitulation of vote counts in Deli Serdang Regency during the 2019 Election caused disruption to the process at the stage of election implementation at the North Sumatra Province level, even though based on the 2019 Election stages the delay did not interfere with the national recapitulation process. However, on a regional and local scale this can lead to public distrust of the performance and integrity of the KPU and in the end it can lead to the emergence of local scale conflicts among election participants who are both anxiously awaiting the vote count results. From the results of the research that the author conducted to see the delay in recapitulation of vote counts in Deli Serdang Regency in the last 2019 Election. The author uses the assumption to test that the delay is caused by 3 factors, namely the election organizer integrity factor, the workload factor and the election organizer competency factor